Global resource availability and utilization of rubberwood - Albaladejo J L (In: Proceedings of the Global Forum on Investment Opportunities in the Indian Rubberwood Industry, 19-21 March 1996, Cochin, India, 1996, pp. 1-17., 1996)
This paper is based on a study of the world supply potential of rubberwood for which data were collected from 15 countries through field visits. The objective of the study was to cross verify the data obtained from various sources and to design an appropriate methodology for the preparation of wood production estimates. The world's rubber plantation area is estimated at 9 million ha., of which more than 90 percent is located in Asia. An important aspect having bearing on the future supply of both natural rubber and rubberwood is that while African and Latin American countries aim at the expansion of plantation area and production, countries like Malaysia and Sri Lanka show a decreasing treand in growing rubber since the 1970s. Other factors that constrain the future supply potential are the predominance of smallholders, poor infrastructure facilities and inaccessible locations of plantations, insufficient replanting programmes, etc.
Keywords: Rubberwood industry; Rubberwood prices; Rubberwood production